The Impact of Information and Communication Technology on Pedagogy: Benefits, Issues, and Challenges - Maria Corazon Saturnina A Castro (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2019)
Information, Communication, and Technology (ICT) in education refers to the use of computer-based communication that incorporates into classroom instructional process (Ghavifekr and Rosdy, 2015). Technologies like computers, internet, broadcast technology are used to improve the effectiveness of the teaching and learning processes. Both teachers and students benefit from ICT. ICT in the classroom can result in higher learner motivation and can facilitate the transmission of basic skills. In addition, independent learning is supported by ICT. On the part of the teachers, it has been noted that many teachers view ICT as something that can assist them in the teaching process. Most teachers are of the opinion that the use of ICT helps them improve teaching through updated teaching and research materials accessed online. These materials allow them to design more interesting lessons and activities for the students. They also enable teachers carry out research beyond physical borders. Despite the benefits that the use of ICT in classroom brings, there are issues and challenges that need to be addressed. Among these are 1) lack of technological skills on the part of the teachers; 2) lack of technological tools/equipment; 3) high cost of facilities and infrastructure; 4) lack of technical support. It cannot be denied that ICT plays a significant role in changing the teaching and learning processes for the better. However, teachers must learn new skills that would enable them to adapt to a new and challenging teaching environment. There is also a serious need for a strong government support and institutional commitment to ensure successful and consistent teacher training and to improve ICT infrastructure in schools.Â Keywords: Information, Communication, Technology, Pedagogy/Education